31st Brazilian Online Society for Virology (SBV) 2020 Annual Meeting - Arruda, Luciana Barros de; Campos, Fabrício Souza; Abrahão, Jônatas Santos; da Fonseca, Flávio Guimarães; Araújo Junior, João Pessoa [UNESP]; Rosado Spilki, Fernando (MDPI, 2021)
The year 2020 was profoundly marked by the emergence and spread of SARS-CoV-2, causing COVID-19, which represents the greatest pandemic of the 21st century until now, and a major challenge for virologists in the scientific and medical communities. Increased numbers of SARS-CoV-2 infection all over the world imposed social and travel restrictions, including avoidance of face-to-face scientific meetings. Therefore, for the first time in history, the 2020 edition of the Brazilian Society of Virology (SBV) congress was totally online. Despite the challenge of the new format, the Brazilian society board and collaborators were successful in virtually congregating more than 921 attendees, which was the greatest SBV participant number ever reached. Seminal talks from prominent national and international researchers were presented every night, during a week, and included discussions about environmental, basic, animal, human, plant and invertebrate virology. A special roundtable debated exclusively new data and perspectives regarding COVID-19 by some of the greatest Brazilian virologists. Women scientists were very well represented in another special roundtable called Young Women Inspiring Research, which was one of the most viewed and commented section during the meeting, given the extraordinary quality of the presented work. Finally, SBV offered the Helio Gelli Pereira award for one graduate and one undergraduate student, which has also been a fruitful collaboration between the society and Viruses journal. The annual SBV meeting has, therefore, reached its goals to inspire young scientists, stimulate high-quality scientific discussion and to encourage global collaboration between virologists.
Keywords: antivirals; COVID-19; human virology; veterinary virology; viral diseases; viral epidemiology; viral pathogenesis